En torno a la representación especial indígena en el Perú: percepción de líderes indígenas y características del modelo peruano - Villanueva Montalvo, Aída (2012)
About special indigenous representation in Peru: An approach from the viewpoint of indigenous leaders. Following the numerous indigenous uprisings in the 1990´s, scholars have paid close attention to indigenous politics in Latin America, with their main focus placed on the construction of indigenous movements, as well as indigenous identity. In contrast, very few contributions deal with institutional designs to promote indigenous people’s access to formal politics. This paper addresses the topic of descriptive representation of indigenous people in formal decision-making spheres, with the main focus on the Parliament. It outlines the benefits associated with descriptive representation of minorities, as well as two cases of interest: Mexico and New Zealand. Based on interviews conducted during the summer of 2009, the article provides insight into the indigenous leaders´ assessments regarding this issue. It also includes a look at the magnitude of recent indigenous representation in Parliament. The final section presents a brief review of some strategies to include indigenous people informal power structures.